2019
DOI: 10.1098/rsbl.2019.0360
|View full text |Cite
|
Sign up to set email alerts
|

Experimentally flight-impaired females show higher levels of extra-pair paternity in the pied flycatcherFicedula hypoleuca

Abstract: There is no consensus yet on the reasons why females engage in extra-pair copulations (EPCs). In some species, females have been shown to accrue some indirect benefits, but these effects are not consistent across species and studies. The sexual conflict hypothesis posits that extra-pair paternity (EPP) is the result of strong selection for male pursuit of EPC without real benefits for females. In order to test this hypothesis, we experimentally reduced wing area (reversibly tying together some primary feathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
3
11
0
Order By: Relevance
“…Our experimental results showed that females of the experimental group displayed a higher condition and wing loading as well as higher EPP levels. These results are in accordance with a previous study reported by Plaza et al (2019), in which handicapped females with a diminished flying ability caused by an increased wing loading, also displayed higher EPP levels. Wing loading has previously been negatively correlated with flying capacity and a reduced manoeuvring ability (van den Hout et al 2010;Salewski et al 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our experimental results showed that females of the experimental group displayed a higher condition and wing loading as well as higher EPP levels. These results are in accordance with a previous study reported by Plaza et al (2019), in which handicapped females with a diminished flying ability caused by an increased wing loading, also displayed higher EPP levels. Wing loading has previously been negatively correlated with flying capacity and a reduced manoeuvring ability (van den Hout et al 2010;Salewski et al 2014).…”
Section: Discussionsupporting
confidence: 93%
“…One interpretation of our results would support the role of sexual conflict in the evolution of EPP. This interpretation would explain the patterns as caused by experimental females being less able to escape from unwanted copulations with extra-pair males, thereby increasing their EPP rate (Plaza et al 2019). This is in agreement with a scenario in which the levels of EPP would be influenced by male coercion instead of female choice (Björklund and Westman 1983) and it is consistent with the results found in a non-experimental study by Moreno et al (2015), where a positive association between wing loading and EPP was reported.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Applied Biosystems MagMAX DNA Isolation Kit (Thermo Fisher Scientific, Waltham) was used to isolate the DNA from tissues and blood, following the manufacturer’s protocol. PCR was done using five microsatellite DNA loci: Fhyu336, Fhyu234, Fhyu304, Fhyu453, and Fhyu448 ( 28 , 43 , 44 ). Applied Biosystems 3130xl Genetic Analyzer (Thermo Fisher Scientific, Waltham) was used to separate the PCR product fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Although the majority of species are socially monogamous, copulations outside the social pair bond are widespread and cause varying levels of EPP ( Griffith et al 2002 ; Westneat and Stewart 2003 ; Brouwer and Griffith 2019 ). Extrapair copulations will typically benefit males because they can sire additional offspring, but the adaptive value of extrapair behavior for females remains controversial ( Forstmeier et al 2014 ; Whittingham and Dunn 2016 ; Plaza et al 2019 ). To understand the evolution of EPP and its consequences for sexual selection ( Webster et al 1995 ; Schlicht and Kempenaers 2013 ), we need to find out why males vary in extrapair siring success and why females vary in how many of their eggs are sired by their social mate.…”
Section: Introductionmentioning
confidence: 99%